2004
DOI: 10.12968/jowc.2004.13.3.26590
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing concordance with compression stockings after venous leg ulcer healing

Abstract: Many factors previously thought to influence concordance appear to have little impact on compression-stocking use in people whose venous leg ulcers had healed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
53
2
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 6 publications
8
53
2
5
Order By: Relevance
“…Results of our study confirm the previous findings in this area 26,27,30. However, it was related to CVD duration and severity of symptoms.…”
Section: Discussionsupporting
confidence: 91%
“…Results of our study confirm the previous findings in this area 26,27,30. However, it was related to CVD duration and severity of symptoms.…”
Section: Discussionsupporting
confidence: 91%
“…STSG in our patient population was very effective with 100% graft take and complete healing still evident at 1 year. This is in comparison to venous stasis ulcers treated with unna boot followed by STSG described almost 50% recurrence of the ulcer within 3 months of discharge (24).…”
Section: Key Pointsmentioning
confidence: 64%
“…10,16 One possible explanation is that the typical patient may be unable or unwilling to tolerate these high compression bandages for any length of time or may have difficulty applying them, although we do not have data to support this conclusion. However, Jull et al 17 found that patients were less likely to wear compression dressings/stockings if they considered them uncomfortable. Another possibility is that some staff might not have been skilled in applying the compression bandaging.…”
Section: Discussionmentioning
confidence: 99%